2018
DOI: 10.3390/nu10101554
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Kimchi Improve the Cognitive and Memory Functions Impaired by Amyloid Beta

Abstract: This study investigated the abilities of kimchi and its bioactive compounds to ameliorate amyloid beta (Aβ)-induced memory and cognitive impairments. Mice were given a single intracerebroventricular injection of Aβ25-35, followed by a daily oral administration of capsaicin (10 mg·kg-bw–1), 3-(4′-hydroxyl-3′,5′-dimethoxyphenyl)propionic acid (50 mg/kg bw), quercetin (50 mg/kg bw), ascorbic acid (50 mg/kg bw), or kimchi methanol extract (KME; 200 mg/kg bw) for 2 weeks (n = 7 per group). Carboxymethylcellulose wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Nutrients originating from Kimchi and its ingredients modulate the Nrf2/PERK signalling pathway to homeostasis in oxidative stress states. Kimchi and its bioactive compound ((3–4′‐hydroxyl‐3′,5′‐dimethoxyphenyl) propionic acid: HDMPPA), which is a metabolite result from fermentation, alleviate oxidative stress and inflammatory response not only via the Nrf2 pathway, but also via the PERK/CHOP pathway, which induced apoptosis of ER, in cardiovascular disease and ageing models [100–102 ]. In addition, Arvelexin from Brassica rapa and anthocyanin‐rich extract from red cabbage exert anti‐inflammatory properties by the inhibition of NF‐ κB activation and by Nrf2‐regulated HO‐1 induction in macrophages and apolipoprotein E‐deficient mice [103, 104 ], suggesting that Nrf2 activation during inflammation antagonizes the NF‐κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients originating from Kimchi and its ingredients modulate the Nrf2/PERK signalling pathway to homeostasis in oxidative stress states. Kimchi and its bioactive compound ((3–4′‐hydroxyl‐3′,5′‐dimethoxyphenyl) propionic acid: HDMPPA), which is a metabolite result from fermentation, alleviate oxidative stress and inflammatory response not only via the Nrf2 pathway, but also via the PERK/CHOP pathway, which induced apoptosis of ER, in cardiovascular disease and ageing models [100–102 ]. In addition, Arvelexin from Brassica rapa and anthocyanin‐rich extract from red cabbage exert anti‐inflammatory properties by the inhibition of NF‐ κB activation and by Nrf2‐regulated HO‐1 induction in macrophages and apolipoprotein E‐deficient mice [103, 104 ], suggesting that Nrf2 activation during inflammation antagonizes the NF‐κB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Oral ingestion, or intragastric administration, of fisetin [ 41 ], hesperidin [ 43, 80 ], quercetin [ 58 ], rutin [ 55, 85 ], apigenin [ 24 ], puerarin [ 84 ] or (–)-EC [ 131 ] has been shown to reduce markers of oxidative stress in the brains of mouse models of AD ( Table 1 ). This was demonstrated through increased activity of anti-oxidative enzymes such as GPx, CAT and SOD and a reduction in measurable H 2 O 2 , ROS and malondialdehyde (MDA).…”
Section: Inhibiting Ad Pathology With Flavonoids: Mechanisms Of Actiomentioning
confidence: 99%
“…In this study protein expression of APP and BACE1, elevated by Aβ injection, also tended to decrease by oral administration of 10 mg capsaicin. Furthermore, daily oral administration of bioactive compounds in Kimchi, including capsaicin (10 mg/kg), improved cognitive and memory functions in mice injected with Aβ25-35 98 . Recently it has been shown that TRPV1 activation by capsaicin rescued Aβ-induced degradation of hippocampal gamma oscillations, a cognition-relevant EEG pattern, by reversing desynchronization of AP firing in CA3 pyramidal cells and by reversing the shift in the excitatory/inhibitory current balance 99 .…”
Section: Discussionmentioning
confidence: 96%